Exploring the effectiveness of modified algebra tile media in teaching single-variable linear equations: a case study - Berliana, Adinda Quin; Darmawan, Puguh; Alaiya, Syekha Vivi; Dejarlo, Jenisus O. (Nashir Al-Kutub Indonesia, 2024)
Single-variable linear equations are open mathematical sentences that contain only one variable raised to the power of one and are connected by an equals sign (“=”). This topic is often perceived as challenging by students, highlighting the importance of exploring innovative teaching strategies. This study examines the implementation of modified algebra tile media to enhance student understanding of single-variable linear equations. A qualitative case study approach was employed, involving a subject group consisting of student practitioners and 36 student observers. The research procedure included developing the modified algebra tile media followed by its application in teaching single-variable linear equations. Data were collected using the media, video recording devices, and field notes from the supervising lecturer. Interactive data analysis techniques revealed that the use of modified algebra tile media significantly facilitated students' comprehension of single-variable linear equations. By enabling hands-on manipulation of the media, students no longer needed to rely solely on abstract visualization of variables. These findings suggest that incorporating tangible, interactive teaching tools can effectively address learning difficulties in mathematics, particularly for abstract concepts.